2013
DOI: 10.1186/2193-1801-2-506
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and partial characterization of culture conditions for the production of alkaline protease from Bacillus licheniformis P003

Abstract: Proteolytic enzymes have occupied a pivotal position for their practical applications. The present study was carried out under shake flask conditions for the production of alkaline protease from Bacillus licheniformis P003 in basal medium containing glucose, peptone, K2HPO4, MgSO4 and Na2CO3 at pH 10. The effect of culture conditions and medium components for maximum production of alkaline protease was investigated using one factor constant at a time method along with its characterization. Maximum level of enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
5
22
0
1
Order By: Relevance
“…Thus, enzyme production was found to be markedly influenced by the medium composition, with the ratio of wheat bran in the substrate, Tween‐80, and the moisture content all emerging as important influencing parameters. Some previous studies have shown that suitable concentrations of Tween‐80 in the medium can induce and improve cellulase and protease production (Sarker, Talukdar, Deb, Sayem, & Mohsina, ; Vu, Pham, & Kim, ). Tween‐80 is routinely included in media for promoting cellulase production and preventing the denaturation of cellulolytic enzymes (Castanon & Wilke, ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, enzyme production was found to be markedly influenced by the medium composition, with the ratio of wheat bran in the substrate, Tween‐80, and the moisture content all emerging as important influencing parameters. Some previous studies have shown that suitable concentrations of Tween‐80 in the medium can induce and improve cellulase and protease production (Sarker, Talukdar, Deb, Sayem, & Mohsina, ; Vu, Pham, & Kim, ). Tween‐80 is routinely included in media for promoting cellulase production and preventing the denaturation of cellulolytic enzymes (Castanon & Wilke, ).…”
Section: Resultsmentioning
confidence: 99%
“…Protease production is generally influenced by nutritional factors (carbon and nitrogen sources) and environmental conditions (pH, temperature, and incubation periods). There have been several reports on protease production by various bacteria ( 18 19 20 21 ), including those that have investigated the production of organic solvent-stable proteases ( 4 , 6 ). In our study, peak protease production was observed at 48 h of incubation, after which activity likely decreased owing to nutrient depletion.…”
Section: Discussionmentioning
confidence: 99%
“…; Sarker et al . ). It was found that alkaline media and elevated temperatures reduced the volume of spores, while aeration and agitation rates affected spore cell density (Posada‐Uribe et al .…”
Section: Optimum Cultivation Conditions For Metabolite Productionmentioning
confidence: 97%
“…A number of studies have investigated the influence of cultivation conditions on Bacillus spore production (Posada-Uribe et al 2015;Xu Zhou et al 2017), while others focused on conditions for optimum protease production (Ray et al 2012;Sarker et al 2013). It was found that alkaline media and elevated temperatures reduced the volume of spores, while aeration and agitation rates affected spore cell density (Posada-Uribe et al 2015;Xu Zhou et al 2017).…”
Section: Optimum Cultivation Conditions For Metabolite Productionmentioning
confidence: 99%